Revie ⊕: An intervention promoting the dignity of individuals with advanced cancer: A feasibility study. (April 2019) - da Rocha Rodrigues, Maria Goreti; Pautex, Sophie; Zumstein-Shaha, Maya
Abstract: Purpose: The dignity of patients is a major concern among health professionals engaged in the care of individuals with advanced cancer. Although several dignity promoting interventions have been developed, none of them have focused on a positive, resource-based approach. The aim of our study, entitled Revie ⊕, was to assess the feasibility and acceptability of a theory-guided life-review intervention, focusing on strength and resources, for patients with advanced cancer and for nurses delivering the intervention. Method: Our 2015–2016 study was conducted with patients with advanced cancer in an ambulatory and an inpatient setting of a Swiss university hospital. An embedded concurrent mixed method design was used. The feasibility and acceptability of Revie ⊕ was explored, as were changes in the sense of dignity, posttraumatic growth, and satisfaction with life. Results: A total of 41 patients received the intervention. The level of attrition was low (26%). Administering the Revie ⊕ intervention proved to be feasible. Participants (patients and nurses) considered the intervention helpful with a high level of satisfaction. A merged data analysis highlighted the need to address the patients' existential concerns. The majority of the participants found that the intervention helped them, and they recommend it for other patients. Conclusions: This study indicates that the Revie ⊕ intervention, which focuses on a resource-based approach, was perceived favorably by all of the participants. A change in the nurse-patient relationship was noted and it was deemed to be beneficial. Highlights: Impact statement Why is this research needed? There is a lack of recommendations and guidelines for nurses to alleviate existential concerns of patients with cancer. There is limited evidence of development and feasibility of nursing interventions promoting dignity of patients with cancer. No study of patients with advanced cancer has integrated a positive approach based on a theoretical nursing framework. What are the key findings? The Revie ⊕ intervention was feasible and presented good level of acceptability for both the patients and the nurses. The positive resource-based approach was welcomed by all of the participants. The intervention allowed for a transformation of the patient-nurse relationship. How should the findings be used to influence policy/practice/research/education Future healthcare policies should reinforce the importance of providing a patient-centered positive approach. Health professionals should be aware that they play an important role in promoting the dignity of patients with cancer. There is a need for implementing nursing interventions based on a theoretical nursing framework.